2022
DOI: 10.1038/s41598-022-08646-7
|View full text |Cite|
|
Sign up to set email alerts
|

Digit ratios and their asymmetries as risk factors of developmental instability and hospitalization for COVID-19

Abstract: COVID-19 presents with mild symptoms in the majority of patients but in a minority it progresses to acute illness and hospitalization. Here we consider whether markers for prenatal sex hormones and postnatal stressors on developmental instability, i.e. digit ratios and their directional and unsigned asymmetries, are predictive of hospitalization. We focus on six ratios: 2D:3D; 2D:4D; 2D:5D; 3D:4D; 3D:5D; 4D:5D and compare hospitalized patient and control means for right, and left ratios, directional asymmetrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…2D:5D, 3D:5D, 4D:5D) and also for 2D:4D. The two ratios with the largest effect sizes for these patient-control differences were 2D:4D and 3D:5D and together their composite asymmetry gave a patient-control effect size of d = 1.04 (1).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…2D:5D, 3D:5D, 4D:5D) and also for 2D:4D. The two ratios with the largest effect sizes for these patient-control differences were 2D:4D and 3D:5D and together their composite asymmetry gave a patient-control effect size of d = 1.04 (1).…”
Section: Introductionmentioning
confidence: 89%
“…The study of Kasielska-Trojan et al (1) was limited by lack of knowledge concerning the properties of unsigned digit ratio asymmetries and by the relatively small sample of patients (1). The latter meant that associations between patient asymmetries and laboratory tests might be unreliable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported a subtle difference in the finger length pattern of women with PCOS, but a few studies found no difference for 2D:4D between PCOS and controls. Besides 2D:4D, other ratios of digit length were reported to present sexual differences in humans ( 15 , 16 ). However, previous studies related to digit ratio and PCOS were confined to 2D:4D and lacked evidence of other digit ratios in PCOS.…”
Section: Introductionmentioning
confidence: 99%